Entropy and the value of information for investors - Antonio Cabrales; Olivier Gossner; Roberto Serrano (Brown University, Department of Economics, 2010)
Consider any investor who fears ruin facing any set of investments that satisfy no-arbitrage. Before investing, he can purchase information about the state of nature in the form of an information structure. Given his prior, information structure 'a' is more informative than information structure 'b' if whenever he rejects 'a' at some price, he also rejects 'b' at that price. We show that this complete informativeness ordering is represented by the decrease in entropy of his beliefs, regardless of his preferences, initial wealth or investment problem. It is also shown that no prior-independent informativeness ordering based on similar premises exists.
Keywords: C00; C43; D00; D80; D81; G00; G11; 330; informativeness; information structures; entropy; decision under uncertainty; investment; Blackwell ordering.